Masa Tunggu Suami terhadap ‘Iddah Istri Perspektif Al-Żarῑʻah - Hidayat, Mohammad Shofi; Yusmad, Muammar Arafat; Kamal, Helmi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
This study discusses the Circular Letter of the Director General of Public Guidance of the Ministry of Religion Number P.005/DJ.III/Hk.00.7/10/2021 in which there is a policy on the waiting period of the former husband for the ‘iddah of the ex-wife from the perspective of al-żarῑʻah, so that the basis and purpose of the issuance of the circular letter can be known. This research is a juridical normative legal research with an analytical approach that refers to applicable regulations. Data validity checks using data triangulation methods, observation persistence, and peer checking which are then processed by classification, verification, and analysis to produce conclusions. The results of the study show that ‘iddah is a waiting time that applies to a wife whose marriage is broken up, including for ex-husbands. In general, the content of the policy in this Circular Letter is under the method of preventing badness (sadd al-żarῑʻah). The policy regulates that ex-husbands can only marry other women when the ‘iddah period of their ex-wives has been completed or the ’iddah has ended because this encourages ex-husbands to rethink or as an effort of reconciliation so that the hope is that ex-husbands can reconcile with their ex-wives as recommended by Allah Almighty. If the husband marries another woman, it leads to badness (mafsadat), namely divorce, which is an act that is most hated by Allah Almighty.